Melonhead and the vegalicious disaster - Kelly, Katy (Delacorte Press, 2012)
Can Adam "Melonhead" Melon, who lives in the Washington, D.C., neighborhood of Capitol Hill, survive his fearsome fifth-grade teacher and his mother's resolution to cook healthy, nutritious meals?